Jumping performance differences among elite professional handball players with or without previous ACL reconstruction - Setuain I.; Millor N.; Alfaro, J.; Gorostiaga E.; Izquierdo M. (The Journal of Sports Medicine and Physical Fitness, 2015)
AIM: Handball is one of the most challenging sports for the knee joint. Persistent strength and jumping capacity alterations may be observed among athletes who have suffered anterior cruciate ligament (ACL) injury. The aim of this study was to examine unilateral and bilateral jumping ability differences between previously ACL-reconstructed rehabilitated elite handball athletes and sex, age and uninjured sport activity level-pairs of control players.